Continuous intention to use technology of online food delivery services among young adults / Shahira Ariffin ...[et al.] - Ariffin, Shahira; Abdul Manan, Hasman; Ahmad, Norsiah; Muhammad, Nur Shahrulliza; Hamdan, Fairus; S Kelana, Nur Sabrina (Universiti Teknologi MARA, 2021)
Online food delivery services have experienced tremendous growth in the food industry. Food delivery apps had gathered this opportunity adjusting to restaurant and food delivery services as an alternative to increasing income and for customers to remotely order their foods. This study aims to determine the relationship between information quality, performance expectancy, effort expectancy and social influence with continuous use intention of food delivery apps from Malaysian young adults' context. In this study, a total of 300 sets of questionnaires were successfully collected. The data was interpreted using SPSS Version 25. At the end of the study, it was found that the results of the analysis to be a positive relationship between information quality, performance expectancy and social influence with continuous use intention of food delivery apps among young adults. This study also revealed that social influence as the most influential factor affecting continuous use intention of food delivery apps.